Hot spring sinters: keys to understanding Earth's earliest life forms - Konhauser, Kurt O; Jones, Brian; Reysenbach, Anna-Louise; Renaut, Robin W (Canadian journal of earth sciences, 2003)
The question of what composed the Earth's oldest fossils is the subject of current debate. At present, taphonomical determination of Archean silicified microfossils is largely based on morphological comparisons with extant microorganisms. This method has significant shortcomings because little is known about which types of bacteria silicify, what physical changes are induced on those species during mineralization, and, most importantly, what their preservation potential is. Terrestrial hot springs may help resolve these uncertainties because the silica-supersaturated geothermal fluids mineralize a wide variety of natural microbial communities and thus lead to the formation of numerous distinct biofacies. Some of these biofacies are reminiscent of Archean siliceous stromatolites from which the oldest microfossils were recovered. We suggest that by integrating molecular techniques that characterize the indigenous microbial populations growing in different biofacies with electron microscopy, we may be able to assess better what types of ancient microbes could have become fossilized.